Analysis on the Development Status of Coal Mine Dust Disaster Prevention Technology in China. (20th April 2021) - Zhang, Hui; Han, Weihai; Xu, Youlin; Wang, Zhenfeng
Abstract : In recent years, with the increasing level of mechanization, automation, and intelligence in mine mining, dust pollution in the working environment of coal mines has become increasingly serious. Coal mine dust prevention is an important work related to the life, health, and production safety of miners, and it is also one of the technical problems of mine safety in production. With the continuous revision and improvement of China′s Occupational Disease Prevention and Control Law, coal mining enterprises have generally strengthened the publicity, prevention, and control of occupational diseases among employees, and the control of coal mine dust has been used as a means for enterprises to improve the production environment and strengthen the occupational health of employees. Key work-based studies have shown that China's coal mines have formed a theoretical system and technology system of dust prevention and control. In the future, China's coal mines will start from intelligent dust prevention, achieve high-precision dust sensing-transmission-assessment and early warning, and develop a combined dust collector that integrates the functions of atomization dust removal, miniaturization, dry and wet mixing, and large air suction capacity. The combined dust collector realizes the efficient ventilation control and dust removal of the fine dust in wide-area complex spaces such as fully mechanized mining face and fully mechanized mining face. At the same time, breakthroughs have been achieved in low-permeability coal seams, such as strong hydraulic permeability-enhancing technology, intelligent dust-proof robots, and chemical dust suppression. This article introduces the basic concepts, generation, distribution, and hazards of coal mine dust and analyzes the characteristics, applicable conditions, and use effects of various dust control measures such as ventilation dust removal and wet dust removal. Moreover, this article also proposes specific prevention and control measures for related occupational diseases and discusses the development trend of dust prevention and control technology in the hope of providing guidance and reference for coal mine dust prevention and control.